THE MECHANISM BY WHICH ANTIOXIDANTS PROTECT THE BODY FROM THE EFFECTS OF FREE RADICALS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
The vital processes of the organism are inextricably linked with the formation of reactive oxygen metabolites (ROS) of radical and non-radical origin, which are intermediate products of the four-electron reduction of oxygen to water. ROS participate in two main processes: on the one hand, the implementation of the body's defense mechanisms; on the other hand, excessive formation of ROS and their secondary products leads to a state known as oxidative stress. The development of oxidative stress in the body is prevented by substances with antioxidant properties of endogenous and exogenous origin. Today, it is difficult to find a single area of ​​medicine, biochemistry, biophysics, pharmacy or food technology that would not study free radical oxidation and the antioxidant effect. The study of the antioxidant properties of substances is interdisciplinary and is aimed at improving human health and increasing life expectancy. One of the current directions in this field is the development of approaches to determine the integral parameters of antioxidant and antiradical capacity/activity, since the effectiveness of the body's antioxidant system may not be related to the content of a particular compound, but rather reflects the properties of the entire system.